POLITICAL CULTURE AND PARLIAMENT IN PERU (2011-2016). CORRUPTION IN THE PERCEPTION OF UNIVERSITY STUDENTS IN LIMA - YALLE QUINCHO, Omar (2021)
The purpose of this work is to know the political culture of Parliament in Peru (2011- 2016), based on the perception of university students from four universities in Lima. It is proposed to explore, as a pilot study, the ideas they have regarding parliamentary representation and the ethical and corruption problems of some representatives, as well as the imaginaries that they build around it.